Investigation of S-SPH for Hypervelocity Impact Calculations. (2015) - Stowe, David; Kupchella, Ryan; Pan, Hua; Cogar, John
Abstract: In this paper, we investigate the Symmetric-SPH (S-SPH) method. S-SPH restores n-order consistency to the SPH formulation while remaining fully conservative by using a Taylor expansion of field variables to fit the kernel function. It has potential for HVI problems because it enables the ability to perform accurate stress and state calculations. We implement S-SPH in the Velodyne hydro-structural solver and evaluate its performance over a series of numerical examples including flyer impact, fragment penetration, and Taylor Rod impact. Idealized contact algorithms are employed to eliminate uncertainty in the flyer and Taylor impact problems while an advanced Lagrange multiplier algorithm is used for the fragment penetration test. We use the CTH hydrocode to provide a baseline response for each of the examples due to its ability to effectively handle penetration, hydrodynamic deformation, and shock propagation. Direct numerical comparisons are used to eliminate uncertainty from material characterizations, equation of state (EOS) models, and mesh resolution. We identify strengths and shortcomings of the S-SPH method and evaluate its utility for classes of HVI problems. We also compare the performance against SPH to compare relative accuracy, computational cost, and stability.